Pharmacokinetic and pharmacodynamic considerations in developing a response to the opioid epidemic. (1st February 2020) - Balyan, Rajiv; Hahn, David; Huang, Henry; Chidambaran, Vidya
ABSTRACT: Introduction : Opioids continue to be used widely for pain management. Widespread availability of prescription opioids has led to opioid abuse and addiction. Besides steps to reduce inappropriate prescribing, exploiting opioid pharmacology to make their use safer is important. Areas covered : This article discusses the pathology and factors underlying opioid abuse. Pharmacokinetic and pharmacodynamic properties affecting abuse liability of commonly abused opioids have been highlighted. These properties inform the development of ideal abuse deterrent products. Mechanisms and cost-effectiveness of available abuse deterrent products have been reviewed in addition to the pharmacology of medications used to treat addiction. Expert opinion : The opioid crisis presents unique challenges to managing pain effectively given the limited repertoire of strong analgesics. The 5-point strategy to combat the opioid crisis calls for better preventive, treatment, and recovery services, better data, better pain management, better availability of overdose-reversing drugs and better research. There is an urgent need to decrease the cost of abuse deterrent opioids which deters their cost-effectiveness. In addition, discovery of novel analgesics, further insight into central and peripheral pain mechanisms, understanding genomic risk profiles for efficient targeted efforts, and education will be key to winning this fight against the opioid crisis.